Broadening access to naloxone: Community predictors of standing order naloxone distribution in Massachusetts. (1st January 2022) - Chatterjee, Avik; Yan, Shapei; Xuan, Ziming; Waye, Katherine M.; Lambert, Audrey M.; Green, Traci C.; Stopka, Thomas J.; Pollini, Robin A.; Morgan, Jake R.; Walley, Alexander Y.
Abstract: Background: Naloxone is a prescription medication that reverses opioid overdoses. Allowing naloxone to be dispensed directly by a pharmacist without an individual prescription under a naloxone standing order (NSO) can expand access. The community-level factors associated with naloxone dispensed under NSO are unknown. Methods: Using a dataset comprised of pharmacy reports of naloxone dispensed under NSO from 70% of Massachusetts retail pharmacies, we examined relationships between community-level demographics, rurality, measures of treatment for opioid use disorder, and overdose deaths with naloxone dispensed under NSO per ZIP Code-quarter from 2014 until 2018. We used a multi-variable zero-inflated negative binomial model, assessing odds of any naloxone dispensed under NSO, as well as a multi-variable negative binomial model assessing quantities of naloxone dispensed under NSO. Results: From 2014–2018, quantities of naloxone dispensed under NSO and the number of pharmacies dispensing any naloxone under NSO increased over time. However, communities with greater percentages of people with Hispanic ethnicity (aOR 0.91, 95% CI 0.86–0.96 per 5% increase), and rural communities compared to urban communities (aOR 0.81, 95% CI 0.73–0.90) were less likely to dispense any naloxone by NSO. Communities with more individuals treated with buprenorphine dispensed more naloxone under NSO, as did communities with more opioid-related overdose deaths. Conclusion: Naloxone dispensing has substantially increased, in part driven by standing orders. A lower likelihood of naloxone being dispensed under NSO in communities with larger Hispanic populations and in more rural communities suggests the need for more equitable access to, and uptake of, lifesaving medications like naloxone. Highlights: Naloxone by standing order (NSO) in Massachusetts increased from 2014 to 2018. There are inequities in dispensing NSO based on ethnicity and rurality. More NSO is dispensed in communities with more people receiving buprenorphine. More NSO is dispensed in communities with more opioid-related overdose deaths. NSO has expanded naloxone access but more equitable approaches may be necessary.